2006
DOI: 10.1523/jneurosci.3970-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Loss ofp53Induces Changes in the Behavior of Subventricular Zone Cells: Implication for the Genesis of Glial Tumors

Abstract: The role of multipotential progenitors and neural stem cells in the adult subventricular zone (SVZ) as cell-of-origin of glioblastoma has been suggested by studies on human tumors and transgenic mice. However, it is still unknown whether glial tumors are generated by all of the heterogeneous SVZ cell types or only by specific subpopulations of cells. It has been proposed that transformation could result from lack of apoptosis and increased self-renewal, but the definition of the properties leading to neoplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
182
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(205 citation statements)
references
References 47 publications
21
182
1
Order By: Relevance
“…2C and 2D). These results, taken together, indicate that p53 -/ -NSCs differentiated into neurons at the sacrifice of astrocytes, supporting the conclusion drawn by Armesilla-Diaz et al that p53 plays a negative role in NSC neural differentiation but a positive role in gliogenesis [26,28,30], but are inconsistent with 2 reports showing that p53 deficiency did not alter neural or glia differentiation of NSCs [23,27]. This discrepancy is not less likely to be caused by genetic backgrounds, as similar results were obtained from NSCs isolated from p53 -/ -mice on 129 and C57BL/6 background ( Supplementary Fig.…”
Section: P53 Plays An Active Role In Neurogenesissupporting
confidence: 86%
See 3 more Smart Citations
“…2C and 2D). These results, taken together, indicate that p53 -/ -NSCs differentiated into neurons at the sacrifice of astrocytes, supporting the conclusion drawn by Armesilla-Diaz et al that p53 plays a negative role in NSC neural differentiation but a positive role in gliogenesis [26,28,30], but are inconsistent with 2 reports showing that p53 deficiency did not alter neural or glia differentiation of NSCs [23,27]. This discrepancy is not less likely to be caused by genetic backgrounds, as similar results were obtained from NSCs isolated from p53 -/ -mice on 129 and C57BL/6 background ( Supplementary Fig.…”
Section: P53 Plays An Active Role In Neurogenesissupporting
confidence: 86%
“…An active role for p53 in NSC proliferation and cell fate determination A role for p53 in NSC differentiation is still debatable as some studies showed that p53 inhibits neural differentiation, whereas the others did not find such a role [26][27][28]. To further clarify this issue, we isolated NSCs from brains of day 13.5 p53…”
Section: P53 Plays An Active Role In Neurogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…These modifications directly affect the transcriptional activity of p53 and regulate its affinity for diverse cofactors, which in turn regulate the occupancy of p53 in specific promoters [81]. In adult NSCs in the SVZ of p53-deficient mice, loss of p53 was not sufficient for tumour formation, but led to increased cell proliferation and altered differentiation under physiological conditions [82]. p53 was not essential to promote cell death in any of these studies, which also supports the idea that p53 is required to maintain the physiological proliferation rate in NSCs.…”
Section: Cell-intrinsic Epigenetic Mechanisms Targeted By Cell-cycle mentioning
confidence: 99%